(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The current economic recession and rising cost of building materials in Nigeria has created a severe decline in housing affordability for Nigerians. On this account, this research aimed to assess the acoustic property of Saw-dust and Fine Sharp Sand (SFSS) and its application for the fabrication of purpose made Sound-proof Security Doors (SPS-Door). The ingenuity of the research is to offer an alternative fabricated door to the high priced foreign made sound-proof security doors that are not affordable to most Nigerian for housing delivery. The wooden sawdust mixed with fine sharp as a core in-fill material for the door are readily available as natural material and environment waste. Model Sample Panels (MSP) infills produced and tested at the Acoustic Laboratory for noise absorption capacity as established by ASTM E 1050-98 international standards. The research findings revealed that the MSP infills for the SS-Door scored 0.78 to 0.92 for the frequency ranges 50Hz to 5000Hz while foreign Turkey doors infill’s Noise Absorption Coefficient is 0.95 for the same ranges of frequencies. Comparatively, MSP infill is a sustainable and alternative material for the locally fabricated sound-proof security door to the expensive imported brands. In addition, properties of SFSS at the ratio of 5:1 presented high porosity characteristic which had a significant effect on the sound absorption properties of SS-Door. Therefore, architects could specify this innovative infill product for doors panel, walls cavity and floor inside layer for the spaces that require sound insulation and security in the building construction.